Identifying adaptation strategies to climate change for Mediterranean olive orchards using impact response surfaces. (November 2020) - Cabezas, J.M.; Ruiz-Ramos, M.; Soriano, M.A.; Gabaldón-Leal, C.; Santos, C.; Lorite, I.J.
Abstract: The identification of agricultural adaptation strategies to offset climate change impact requires a detailed knowledge of the response of crop systems under future climatic conditions. To carry out such an analysis for Mediterranean olive orchards, an improved version of the AdaptaOlive simulation model combined with perturbed climate (PC) and sensitivity analysis using impact response surfaces (IRSs) have been applied. As a result, phenology, crop yield and irrigation requirements were projected for olive orchards located at five locations representative of Southern Spain, with contrasting current and future weather conditions. Thus, under near future conditions using Representative Concentration Pathway (RCP) 4.5, large differences in olive yield response were found depending on the location, with an average yield increase of 19% for locations with cold winters, and reductions of 34% for locations with mild winters. Olive yield response could show abrupt changes even for limited changes in weather variables when critical thresholds are exceeded. IRSs and PC enabled the identification of such site-specific thresholds in terms of changes in temperature and rainfall from the baseline conditions. Thus, temperature increases of 3 °C generated null crop damage linked to flowering failure caused by lack of chilling in Jaen or Granada, whereas in Seville the damage was severe in 74% of the years. The analysis of the impacts of water stress and temperature increase on olive yield revealed the critical processes that need to be addressed by promoting adaptation measures. Said processes were not the same for entire analyzed area; in Seville —which has mild winters— cultivars with an earlier flowering date should be recommended, but in Granada —which has cold winters and low rainfall— the introduction of deficit irrigation strategies would be the appropriate recommendation. These results confirm the need to conduct weather sensitivity analyses, as provided by PC and IRSs, in order to develop site-specific adaptation strategies for the Mediterranean olive orchards. This procedure was required due to the non-smooth response to weather components, and the high spatial variability of weather conditions and olive orchard characteristics in Southern Spain. Highlights: The impact of climate change on Mediterranean systems showed high spatial variability. Chilling, heat and water stress were the key drivers of the impact on olive orchards. This was assessed combining perturbed climate and impact response surfaces. The source of these impacts differed depending on the location. Site-specific adaptation strategies are required depending on the climatic conditions.